Program Report: KidneyPRO, a Web-based Training Module for Patient Engagement in Kidney Research. (December 2020) - Getchell, Leah; Bernstein, Eva; Fowler, Elisabeth; Franson, Linnea; Reich, Marian; Sparkes, Dwight; Desjarlais, Arlene; Banai, Sara; Pollock, Graham; Lord-Fontaine, Stephanie; Settee, Craig; Robinson-Settee, Helen; et al.
Purpose of report: Over the recent years, there has been increasing support and traction for patient-oriented research (POR). Such an approach ensures that health research is focused on what matters most: improving outcomes for patients. Yet the realm of health research remains enigmatic for many patients in Canada who are not familiar with research terms and practices, highlighting the need for focused capacity-building efforts, including the development of novel educational tools to support patients to meaningfully engage in the research enterprise. The need for disease-specific training in POR was identified by the network dedicated to advancing patient-oriented kidney research in Canada, Canadians Seeking Solutions and Innovations to Overcome Chronic Kidney Disease (Can-SOLVE CKD), during the early years of the network's inception. In this report, we describe the development of KidneyPRO, an online learning module that orients patients and families to kidney research in Canada, and outlines ways to get involved. In line with the Patient Engagement framework of the Strategy for Patient Oriented Research, KidneyPRO was co-developed with the network's patient partners. Sources of information: The need for KidneyPRO was identified through a review of feedback from network participants of Canadian Institutes of Health Research's (CIHR) Foundations in Patient-Oriented Research Module 2—Health Research in Canada and a network-wide survey of Can-SOLVE CKD that was conducted in June 2017 and assessed training needs of key stakeholders. This 2017 survey ranked the need for tools providing introductory knowledge on Canadian kidney research as third in the network's top 5 capacity-building priorities. Methods: At Can-SOLVE CKD, a dedicated multi-stakeholder team was formed from the Training & Mentorship Committee (the network's core infrastructure for POR capacity building) to determine the learning objectives, content, and user interface. The team consisted of 3 patient partners, Director of Research for the Kidney Foundation of Canada, a kidney clinician-scientist, the network's Patient Partnerships & Training Lead, Can-SOLVE CKD's Indigenous People's Engagement and Research Council Coordinator, and a project coordinator. With permission, content from CIHR's Foundations in Patient-Oriented Research, along with resources from the Kidney Foundation of Canada's research arm and network project teams, was used to form the basis of the tool. The working group adapted a DoTTI (Design and develOpment, Testing early iterations, Testing for Effectiveness, Integration, and implementation) framework and iteratively identified, created, and refined the content and user interface in consultation with the Training and Mentorship Committee and the Can-SOLVE CKD Patient Governance Circle. Key findings: In this article, we describe the development, deployment, and evaluation of KidneyPRO, a web-based training module that helps patients understand general, patient-oriented, and kidney-specific research within Canada. KidneyPRO aims to support patient engagement in studies as partners and/or participants and empower them to take part in the research process in an active and meaningful way. It was co-designed and vetted by patients, which helps to ensure clear, useful content and a user-friendly interface. In addition, the module includes links to kidney research opportunities within the Can-SOLVE CKD Network and beyond. A literature review established that KidneyPRO fills an important gap in kidney-specific POR. Ongoing collection of website metrics and postcompletion surveys from users will be used to evaluate the effectiveness of the tool. Limitations: As an online tool, people who do not have adequate Internet access will not be able to use KidneyPRO. Currently, the tool is not compliant with all Web Content Accessibility Guidelines. Given how the landscape of patient partnership in research is constantly evolving, the content in KidneyPRO needs to be updated on a regular basis. Implications: Canadians with or at high risk of CKD now have access to an educational tool when seeking to engage as partners and/or participants in innovative kidney research.